Предмет: Алгебра,
автор: bajdaknatasa0
Розв'яжіть рівняння: ( х - 3 ) ( х + 3 ) - 4х = ( х - 1 ) ² - 5
Ответы
Автор ответа:
3
Объяснение:
х^2 - 9 - 4*х = х^2 + 1 - 2*х - 5
-9 - 4*х = 1 - 2*х - 5
-(2*х +4) = -(9+4*х)
2*х + 4 = 4*х + 9
4*х - 2*х = 4-9
2*х = -5
х = -5/2 = -2.5
Похожие вопросы
Предмет: Русский язык,
автор: Эдуард1111111111
Предмет: Қазақ тiлi,
автор: nikitaylin2005
Предмет: Английский язык,
автор: kadiass
Предмет: Литература,
автор: xhhfjdjАмфе
Предмет: Геометрия,
автор: epicsilence